RELEVANSI NILAI PENDIDIKAN ETIKA DALAM GEGURITAN PATI JLAMIT - Dwi Oktaviana (Sekolah Tinggi Agama Hindu Dharma Nusantara Jakarta, 2021)
Bali has many classic manuscripts that are the heritage of ancestors in the past. The various works of classical literature have the values of Hindu religious education that can be used as an educational medium to guide and guide mankind in achieving happiness and inner harmony. One of the literary texts is the geguritan Pati Jlamit. Geguritan Pati Jlamit is a literary work of Ida Bagus Ketut Sudiasa who was examined to become a priest, later titled Ida Pedanda Ketut Sidemen. This poem is made in the form of a song tied by the lingsa with six types of pupuh, namely pupuh sinom, pupuh pucung, pupuh ginada, pupuh semarandana, pupuh dangdang, and pupuh pucung. The specialty of Geguritan Pati Jlamit which is interesting to study is in its content which is a text loaded with religious values that need to be disseminated to the community in order to increase the sense of devotion to God. One of the values that will be discussed in this study is the value of ethics or morality.